Iluminação eficiente: análise da substituição de lâmpadas fluorescentes tubulares por lâmpadas led em uma instituição pública de ensino - Lima, Felipe Arthur Sabino Araújo (Universidade Federal Rural do Semi-Árido, 2017)
This work presents a study about energy efficiency on lighting in an educational institution. The aim is to determine the technical and economic feasibility of LED lamps insertion in Campus Apodi IFRN as a way to reduce electricity costs, following the guidelines of Ordinance no. 370 of the Ministry of Education. The methodology consisted in quantify loads on the spot, luminotechnical study using DIALux software, proposal to replace existing lighting for LED and analysis of economic viability. The results indicate that it is possible to achieve an energy saving up to 50,352 kWh per year, resulting in annual savings of R$ 26,264 (US$ 7,858). The investment for the retrofit is about R$ 40,632 (US$ 12,312), the simple payback of this project will be achieved in a period of 1 year and 7 months. Therefore, it is feasible to implement
Monografia
Keywords: Eficiência energética; Iluminação; Redução de custos com energia; Retrofit; DIALux; Energy efficiency; Lighting; Energy savings; ENGENHARIAS::ENGENHARIA CIVIL